Without any other information the answers could be a and c because they contain the factor x+5
f(-5)=0 means that x=-5 is a zero which means x+5 is a factor
Without any other information f can be any of the expressions that have the factor (x+5)
A. (x-2)(x+5)(x-3) is the correct answer to this question
Hope it helps!
If f(–5) = 0, what are all the factors of the function f(x)= x^3-19x+30
f(-5)= 0, so x=-5
when x=-5 the value of function is 0 so (x+5) is a factor
Now we use synthetic division
-5 1 0 -19 30
-5 25 -30
1 -5 6 0
Use the answer to get new expression
1x^2 -5x +6 =0
So the factors are (x-3)(x-2)(x+5)
We are given that f(x) = .
Now, f(-5)=0 i.e. (x+5) is a factor of f(x),
We need to find the other two factors.
So, using Remainder Theorem, we get that f(x) is simplified into f(x) = * ().
Now, after solving the quadratic equations, we get that,
f(x) = (x+5)*(x-2)*(x-3).
Hence, a) (x-2)(x+5)(x-3) are the factors of f(x).
If f(-5)=0, then x+5 is first factor of given polynomial.
1. Divide polynomial by x+5:
2. Factor the trinomial :
correct choice is A.
Step-by-step explanThe right answer for the question that is being asked and shown above is that: "A (x – 2)(x + 5)(x – 3)." If f(–5) = 0, the factors of the function f(x) = x^3 - 19x + 30 is A (x – 2)(x + 5)(x – 3), using the Remainder Theorem